Macrophages in Chronic Liver Failure: Diversity, Plasticity and Therapeutic Targeting - Singanayagam, Arjuna; Triantafyllou, Evangelos (Frontiers in Immunology, 2021)
Chronic liver injury results in immune-driven progressive fibrosis, with risk of cirrhosis development and impact on morbidity and mortality. Persistent liver cell damage and death causes immune cell activation and inflammation. Patients with advanced cirrhosis additionally experience pathological bacterial translocation, exposure to microbial products and chronic engagement of the immune system. Bacterial infections have a high incidence in cirrhosis, with spontaneous bacterial peritonitis being the most common, while the subsequent systemic inflammation, organ failure and immune dysregulation increase the mortality risk. Tissue-resident and recruited macrophages play a central part in the development of inflammation and fibrosis progression. In the liver, adipose tissue, peritoneum and intestines, diverse macrophage populations exhibit great phenotypic and functional plasticity determined by their ontogeny, epigenetic programming and local micro-environment. These changes can, at different times, promote or ameliorate disease states and therefore represent potential targets for macrophage-directed therapies. In this review, we discuss the evidence for macrophage phenotypic and functional alterations in tissue compartments during the development and progression of chronic liver failure in different aetiologies and highlight the potential of macrophage modulation as a therapeutic strategy for liver disease.